Tanggung Jawab Dan Kewenangan Pemerintah Daerah Dalam Pelayanan Sosial Melalui Lembaga Kesejahteraan Sosial Di Provinsi Riau - Mohamad Zainuri (Jurnal Kebijakan Pembangunan dan Inovasi, 2019)
This study aims to analyze the responsibilities and authority of the government, the public and the private sector in social services to Persons with Social Welfare Problems (PMKS) through the Social Welfare Institution (LKS) The implementation of social welfare is carried out through the LKS and non (external) LKS models. The implementation of social welfare is carried out through the LKS and non (external) LKS models. Research methods, research locations Riau Province. The method used is the study of literature. The results of this study are the responsibility of the provincial government in allocating a budget for the implementation of social welfare in the regional income and expenditure budget on social services for PMKS which by the Government of Riau Province through 4 LKS in 2018 amounted to 210 people. While the authority in carrying out cooperation and coordination in the implementation of social welfare is not yet proportional. There is a difference of 4.3% of the number of PMKS served by the province less than that of the community. Compared to the total number of PMKS in Riau Province, the implementation of social welfare through LKS is only 0.04%. While the other central government carried out as many as 185 people and the private sector. Private LKS contribute 0.94% of the total PMKS in all Riau Provinces. The conclusion is that the government has the responsibility and authority for the implementation of social welfare through LKS and non-LKS.